Development of a new porous metal support based on nickel and its application for Pd based composite membranes. (2nd March 2015) - Kim, Sung Su; Xu, Nong; Li, Anwu; Grace, John R.; Lim, C. Jim; Ryi, Shin-Kun
Abstract The integrity and performance of Pd-based membranes depends heavily on the properties of the substrate. This study presents the development of a new planar Ni-based porous support for Pd composite membranes. Ni powder was mixed with a 0.1 wt% of Ti and Cu, which have different melting temperatures, and was later uniaxially pressed in a metal mold to make substrate. The pressed substrates were heat treated at 1223 K in a hydrogen environment for 2 h. The pore size and its uniformity were determined using a mercury porosimeter. Adding 0.1 wt% of Ti sufficiently prevents sintering of metal and results in a good pore size distribution. With the aid of a pretreatment, i.e., polishing, etching and alumina coating, and electroless plating, a 9.3-μm-thick Pd membrane could be fabricated on the Ni–Ti substrate, exhibiting a H2 permeation flux of ∼0.1445 mol m−2 s−1 with selectivity (H2/He) of ∼1600 at 723 K and a pressure difference of 100 kPa.